Data-Driven Decision Making in Agriculture with Sensors, Satellite Imagery and AI Analytics by Digital Farming - , Arijit Ghosh; , Sumit Rai; , Ashoka, P; , Kiran Kotyal; , Sabarinathan B; , Saty Saran; Anjali,; K.P.Sivakumar,; , Narinder Panotra; , Shivam Kumar Pandey (Archives of Current Research International, 2025)
Digital technologies are revolutionizing agriculture by enabling data-driven decision making. A combination of sensors, satellite imagery, and AI analytics is providing farmers with unprecedented insights to optimize crop management. Sensors monitor soil moisture, temperature, and nutrient levels in real-time. High-resolution satellite images track crop health, growth stages, and yield potential. Machine learning algorithms process this data to generate actionable recommendations on irrigation, fertilization, pest control, and harvest timing. Case studies demonstrate how these technologies have increased yields, reduced inputs, and improved sustainability on farms worldwide. However, challenges remain in technology adoption due to high costs, lack of digital literacy, and data privacy concerns. Overcoming these barriers will be crucial to harnessing the full potential of digital farming. This paper reviews the current state of digital technologies in agriculture and discusses future research directions to advance data-driven decision making on farms.